(untitled) (Transport systems and technologies, 2023)
The analysis of scientific publications related to the guiding of wheelsets of railway rolling stock along the rail track has been carried out. It is stated that for a valid simulation of the guiding of wheelsets by a rail track, an accurate description of the contact forces of adhesion is necessary. It was found that the flange wheel-rail contact exists only in combination with the angle of attack and in the presence of a lateral cohesive force. A scheme of power interaction of a wheelset with rails with a ridge contact of one of the wheels has been developed. The force contact interaction of a wheel and a rail is a process that is difficult to describe and, at the same time, very important for studying the dynamics of the frictional interaction of vehicles and track and the guiding of vehicles by the rail track. In the general case, the contact of the wheel with the rail occurs in two contact zones: on the rolling surface and on the flange. Simplified, the contact is considered as a two-point contact. The considered force factors cannot be unambiguously attributed to guiding factors or factors of resistance to movement. Specific values and guiding of forces and moments depend on the position of the wheelset relative to the rail track. It is argued that the longitudinal and transverse slips of the wheelsets cause resistance to movement and are overcome by guiding forces.